The cerebellar cognitive affective syndrome scale reveals early neuropsychological deficits in SCA3 patients - Roderick P.P.W.M. Maas; Sven Killaars; Bart P.C. van de Warrenburg; Dennis J.L.G. Schutter (2021)
Abstract Background The cerebellar cognitive affective syndrome scale (CCAS-S) was recently developed to detect specific neuropsychological deficits in patients with cerebellar diseases in an expedited manner. Objectives To evaluate the discriminative ability of the CCAS-S in an etiologically homogeneous cohort of spinocerebellar ataxia type 3 (SCA3) patients and to examine relationships between cognitive deficits and motor symptom severity. Methods The CCAS-S was administered to twenty mildly to moderately affected SCA3 patients and eighteen healthy controls matched for age, sex, and educational level. Disease severity was measured by the Scale for the Assessment and Rating of Ataxia (SARA), Inventory of Non-Ataxia Signs (INAS), 8 m walk test, nine-hole peg test (9HPT), and Patient Health Questionnaire-9 (PHQ-9). Results SCA3 patients had a lower total CCAS-S score ( p < 0.001) and higher number of failed tests ( p = 0.006) than healthy controls. Patients displayed impairments in semantic fluency, phonemic fluency, category switching, cube drawing, and affect regulation. Total CCAS-S score showed high discriminative ability (area under the curve [AUC]: 0.96) and was associated with disease duration, SARA score, walking speed, and dominant hand 9HPT performance. No correlations were observed with INAS count, repeat length, and PHQ-9 score. Discriminative capacity of the number of failed tests was moderate (AUC: 0.76). Conclusion Essentially all SCA3 patients exhibited some form of cognitive impairment. The CCAS-S differentiates SCA3 patients from healthy controls, detects neuropsychological deficits early in the disease course, and correlates with relevant ataxia severity measures.